Temperature-Sensitive Formation of the DNA Replication Complex in Adenovirus 31-Infected Cells - Suzuki, Eiko (1974)
A temperature-sensitive mutant of adenovirus 31 was defective in formation of the DNA replication complex, suggesting the existence of a virus-coded protein necessary for the complex-formation.